2010
DOI: 10.1007/s11270-010-0489-7
|View full text |Cite
|
Sign up to set email alerts
|

Degradation by Solar Radiation of Estrogenic Hormones Monitored by UV–Visible Spectroscopy and Capillary Electrophoresis

Abstract: This work aims to study the degradation of estrone, 17β-estradiol, 17α-ethinylestradiol, and estriol under direct solar radiation, with an average irradiance value of 5.2 kWh/m 2 . Degradation at different temperatures (4°C, 20°C, and 30°C) was also tested in darkness. Individual solutions of the four estrogens were prepared and subjected to the conditions referred to above. The degradation for each compound was followed, after 7, 14, 21, 28, 35, 63, 91, and 126 days measuring the absorbance at the wavelength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 12 publications
0
9
0
1
Order By: Relevance
“…Hence, there is an increased need of developing new analytical tools to facilitate the routine analysis of EDCs in complex matrices, such as biological and environmental ones. Currently, there are several analytical techniques available for the detection of phenolic estrogenic compounds, such as mass spectrometry 1219, coupled or not with liquid or gas chromatography, HPLC 2024, and UV‐vis spectroscopy or capillary electrophoresis 25,26. They have been successfully employed to detect phenolic estrogen compounds at low levels in water, wastewater, effluents, and biological samples.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, there is an increased need of developing new analytical tools to facilitate the routine analysis of EDCs in complex matrices, such as biological and environmental ones. Currently, there are several analytical techniques available for the detection of phenolic estrogenic compounds, such as mass spectrometry 1219, coupled or not with liquid or gas chromatography, HPLC 2024, and UV‐vis spectroscopy or capillary electrophoresis 25,26. They have been successfully employed to detect phenolic estrogen compounds at low levels in water, wastewater, effluents, and biological samples.…”
Section: Introductionmentioning
confidence: 99%
“…Direct solar irradiation was also studied for the degradation of 17β-estradiol, 17α-ethinylestradiol and estriol, with an average irradiance value of 5.2 kWh/m 2 [70]. Authors observed that after 126 days, the degradation rate varied between 75% and 100% and significant changes in the shape of UV-Vis spectra were also observed.…”
Section: Uv Based Processesmentioning
confidence: 99%
“…目前关于雌激素 的紫外光及紫外-可见光降解的研究较多, 这些报道 纷纷指出了光氧化降解在去除类固醇雌激素上的实 用性. 如经 126 天的自然阳光照射, 水溶液中的 E1, E2, E3 和 EE2 去除率达 75%~100% [112] ; E1 和 EE2 在 UVA 波段分别处理 68 和 195 min 后, 雌激素活性降 低了 50% [111] ; 雌激素的光降解过程中若添加一定量 的 TiO 2 则需的能量更少, 初始浓度为 1 μmol L −1 的 E2 溶液中若添加 1 g L −1 的 TiO 2 , 于 18 mJ cm −2 的紫 外灯作用下 3 h 后将全部转化成 CO 2 [30] ; 有研究采 用了 250 W 的紫外灯, Fe(Ⅲ)和 H 2 O 2 协同光降解 系统, 使初始浓度为 18.5 μmol L −1 的 E1 在 160 min 内降解率达 98%以上 [81] . 另外, Liu 和 Liu [ [29,113~115] .…”
Section: 光氧化降解unclassified